2002
DOI: 10.1103/physrevb.66.214101
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of soft mode behavior near the Burns temperature in thePbMg1/3Nb2/3

Abstract: Inelastic neutron scattering measurements of the relaxor ferroelectric PbMg 1/3 Nb 2/3 O3 (PMN) in the temperature range 490 K Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 28 publications
2
41
1
Order By: Relevance
“…It was proposed by Burns that these PNR are formed at some temperature T d (now usually called Burns temperature) much higher than T g [5], for instance, in the case of PMN T d ~ 630K. Recently it was demonstrated that the formation of the PNR is related to the transverse optic (TO) mode softening [6][7][8][9]. The most striking difference of the PNR in relaxors from the precursor clusters in majority of compounds undergoing a structural phase transition is the essential difference of the eigenvectors of the soft mode and PNR.…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed by Burns that these PNR are formed at some temperature T d (now usually called Burns temperature) much higher than T g [5], for instance, in the case of PMN T d ~ 630K. Recently it was demonstrated that the formation of the PNR is related to the transverse optic (TO) mode softening [6][7][8][9]. The most striking difference of the PNR in relaxors from the precursor clusters in majority of compounds undergoing a structural phase transition is the essential difference of the eigenvectors of the soft mode and PNR.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, adjusting the a, b and p parameters allows us to modify the distribution of the points freely, and therefore to include the knowledge of an expert into the LH sampling method. Such knowledge in our case is, for example, the choice of the proper reciprocal lattice vector τ (in [3], it is (3,0,0)) to clearly observe the soft mode. In particular, the authors of [3] have shown that observation of the soft phonon mode in PMN is much easier (as compared to previous results performed in the Brillouin zone centered at (2,0,0)) in the [010] direction near the (3,0,0) reciprocal lattice vector.…”
Section: The Optimization Of Planning Of Experiments By Modified Lhs Mmentioning
confidence: 99%
“…Note that most often the neutron scattering measurements in relaxors are performed for τ = (2, 0, 0) and (3,0,0) (see, e. g. [3,8]). We will use this fact below for planning experiments by the LHS method.…”
Section: Neutron Scattering Lineshape Of the Disordered Dielectricmentioning
confidence: 99%
See 2 more Smart Citations